Syntactic and semantic variation in copular sentences insights from classical Hebrew - Wilson, Daniel J. (Linguist) (Linguistik aktuell ;, 2020)
"This book presents a novel account of syntactic and semantic variation in copular and existential sentences in Classical Hebrew. Like many languages, the system of Classical Hebrew copular sentences is quite complex, containing zero, pronominal, and verbal forms as well as eventive and inchoative semantics. Approaching this subject from the framework of Distributed Morphology provides an elegant and comprehensive explanation for both the syntactic and semantic variation in these sentences. This book also presents a theoretical model for analyzing copular sentences in other languages included related phenomena- such as pseudo-copulas. It is also a demonstration of what can be gained by applying modern linguistic analyses to dead languages. Citing and building off previous studies on this topic, this book will be of interest to those interested in the theoretical examination of copular and existential sentences and to those interested in Classical Hebrew more specifically"--